Antara Inovasi dan Eksploitasi: Strategi Menghadapi AI Face Swap dalam Deepfake Pornografi Non Konsensual melalui website AI detector berbasis Pendekatan Restorative Justice - Laula Albiya; Jessica Priscilla Pardede; Syifa Raudia Syahputri; Muhammad Adymas Hikal Fikri (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The development of artificial intelligence (AI), particularly face swap technology, has provided significant benefits while also generating new forms of digital crime, namely non-consensual deepfake pornography. This practice constitutes a serious violation of privacy, human dignity, and victim protection, especially affecting women and children. This research aims to develop an innovation and exploitation-prevention strategy through the creation of an AI detector website based on a restorative justice approach. The study employs a Research and Development (R&D) method using the Four-D model (Define, Design, Develop, Disseminate). It integrates technical deepfake detection mechanisms, artificial intelligence ethics, and a legal framework oriented toward victim recovery. The expected outcome is an AI detector website that is effective, ethical, and justice-oriented, while also serving as an alternative model for handling digital sexual crimes beyond purely punitive measures. This research contributes to strengthening legal protection and fostering a safer, fairer, and more ethical digital environment in Indonesia.